بچوں پر تشدد کے اسباب و محرکات: سماجی اور ثقافتی عوامل کا جائزہ: Causes and Motivations for Child Abuse: An Analysis of Social and Cultural Factors - Muhammad Aslam Khan; Mahmood ul Hasan; Ahsan Ilahee (International Research Journal of Arabic and Islamic Studies, 2024)
The issue of child abuse and neglect is a global concern that transcends borders and cultures. Various social and cultural factors contribute to this alarming phenomenon. Children, being a vulnerable part of society, are often subjected to violence that can result in severe physical and psychological harm, or even death. This study delves into the myriad reasons behind child abuse, examining the sociocultural dynamics that perpetuate such behavior. Factors such as economic stress, lack of education, cultural norms, and insufficient legal protection play a significant role in the prevalence of child abuse. The impact of these factors is analyzed to understand how they influence the treatment of children within different societies. By identifying the root causes and motivations for child abuse, this research aims to shed light on the complex interplay of social and cultural elements that contribute to this critical issue. Ultimately, the goal is to provide insights that can inform policies and interventions to protect children and promote their well-being globally.